Strategi Kepala Sekolah dalam Memotivasi Guru dalam Meningkatkan Kedisiplinan - Mira Lestari, Kurnia; Sesmiarni, Zulfani; Aulia Gusli, Ramadhoni (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
To improve the discipline of teachers, a brave head of school and forward-thinking is very important to motivate teachers so that teachers in educational institutions are more disciplined. Then a teacher must be cylindrical so that the student can follow the teacher's example. In some cases, researchers observed that the researchers wanted to research how the head of the school's strategy in motivating teachers to improve the discipline of teachers at SMAN 3 Bukittinggi. This study describes the head of the school's approach to motivating teachers to improve teacher discipline. This research was done at SMAN 3 Bukittinggi. This research uses qualitative descriptive methodology with a case study approach. The data collection methods used in this study involve the use of observations, in-depth interviews, and documentation. Activities involved in data analysis include data minimization, data display, and conclusion/verification. The research is located in SMAN 3 Bukitinghigh. Research findings show that the head of school uses six ways to motivate teachers to improve teacher discipline. These strategies include inspiring techniques, leading by example, setting orders, giving supervision, issuing warnings or punishments, and offering incentives.